Justification of Competitive Pricing on Machine-Building Production - V. I. Pokhabov; I. O. Laputsko (Наука и техника)
The paper gives methodology and methods of setting prices on tractors. The basic principle of the methods takes into account dependence of the most important design, operational and ergonomic factors on the market prices of local and foreign tractors. These methods may be applied to justify competitive prices on industrial production and products of other branches of the economy of the Republic of Belarus. The implementation of these methods will make it possible to increase price competitiveness of the target products.